Influência de variáveis ambientais e espaciais na distribuição geográfica da família Cactaceae no leste do Brasil - Santos, Marianna Rodrigues (2009)
This paper was realized with aim of investigate the influence of climatic-environmental and spatial variables and six different vegetation formations on the cacti flora in eastern Brazil. Species occurrence and variables were extracted from bibliography and data banks and after were submitted to Canonical Correspondence Analysis (CCA), Detrended Correspondence Analysis (DCA), indicator species (ISA) and species-area curve analysis connecting species and variables through multivariate analysis programs. Analyses connecting species richness and stem growth with climatic-environmental and spatial variables like latitude, altitude and ocean distance also were did. In all the CCAs, the Monte Carlo permutation test denoted highly significatives differences (p<0,05) and the variables precipitation of driest month, climatic regim, leaf flux, latitude and longitude indicated significatives correlations with two first ordination axis. In spite of the significatives correlations of species and some variables, 83,26% of the species variation was unexplained. Caatinga and savannas and outcrops fields showed the largest number of indicators species, 16,64% and 30,72%, respectively. The analysis of richness distribution showed that cacti flora of eastern Brazil, had a general pattern of intermediary distribution, in agreement with environmental and spatial variables categories analysed here. The cacti stem growth distribution showed be under the influence of the variables analysed, what become interesting the realization of researchs to understand better the relation of cacti flora with its environment.